PENGARUH KONSENTRASI POC NASI BASI TERHADAP PERTUMBUHAN BUNGA KERTAS ORANGE (Bougainvillea spectabilis) - Nicko Andika Putra; Dini Hariyati Adam; Novilda Elzabeth Mustamu; Badrul Ainy Dalimunthe (Agros Journal of Agriculture Science, 2023)
Rice is rice (serelia) that has been boiled or cooked. In general, the color of rice is white if the rice used is white. Rice is a staple food for Indonesian people, because almost all regions in Indonesia consume rice as a staple food. The existence of stale rice is also often found in stalls selling rice besides in the household environment. Stale rice is usually given to livestock, and what is quite interesting is that stale rice is sometimes just thrown in the trash without any further processing, so that it gradually gives an unpleasant smelling effect to the environment and an unpleasant sight. This research will utilize stale rice that comes from the nearest community. There are three kinds of rice waste liquid fertilizer concentrations used, namely concentrations of 10%, 20% and 30% concentrations and there is a control. Fertilizer application is done 2 times a week and maintenance is done by watering every morning and evening with water. Observations were also made twice a week until they were 12 weeks old. The planting medium used to grow paper orange flowers (Bougainvillea spectabilis) is soil. Based on the results of researchers' observations of the height growth of the orange paper flower (Bougainvillea spectabilis) shoots, it is known that the application of various volumes of liquid organic fertilizer to the orange paper flower plants affects the growth of shoot height. Flower plants that experienced quite rapid growth of shoots occurred in P₃ plants with a concentration level of 30% with an average growth of 20.15 mm, while for concentrations of 10% and 20% were 18.94 mm and 19.17 mm, while for the control only 16.8 mm. Keywords: Stale Rice, Organic Fertilizer, Plants, Flowers.INTISARINasi adalah beras (serelia) yang telah direbus atau ditanak. Pada umumnya, warna nasi adalah putih bila beras yang digunakan adalah berwarna putih. Nasi merupakan makanan pokok bagi masyarat Indonesia, karena hampir semua wilayah di Indonesia adalah mengonsumsi nasi sebagai makanan pokoknya. Keberadaan nasi basi juga sering dijumpai di warung-warung penjual nasi selain di lingkungan rumah tangga. Nasi basi biasanya diberikan untuk ternak, dan yang cukup menarik perhatian nasi basi terkadang hanya dibuang begitu saja di tempat sampah tanpa ada pengolahan lanjutan hingga lambat laun memberikan efek bau yang kurang sedap pada lingkungan dan pemandangan yang tidak menyenangkan. Penelitian ini akan memanfaatkan nasi basi yang berasal dari masyarakat terdekat. Ada tiga macam konsentrasi pupuk cair limbah nasi yang digunakan  yaitu konsenrasi 10%, 20% dan konsentrasi 30% serta terdapat kontrol. Pemberian pupuk dilakukan 2 kali dalam seminggu dan pemeliharaan dilakukan dengan cara menyiram setiap pagi dan sore dengan air. Pengamatan juga dilakukan setiap satu minggu dua kali sampai berumur 12 minggu. Media tanam yang digunakan untuk menanam bunga kertas orange (Bougainvillea spectabilis) adalah tanah. Berdasarkan hasil pengamatan peneliti terhadap pertumbuhan tinggi tunas bunga kertas orange (Bougainvillea spectabilis) diketahui bahwa pemberian variasi volume pupuk organik cair kepada tanaman bunga kertas orange mempengaruhi pertumbuhan tinggi tunas. Tanaman bunga yang mengalami pertumbuham tunas cukup pesat terjadi pada tanaman P₃ dengan tingkat konsentrasi 30% dengan rata-rata pertumbuhan sebesar 20,15 mm, sedangkan untuk konsentrasi 10% dan 20% adalah 18,94 mm dan 19,17 mm, sedangkan untuk kontrol hanya sebesar 16,8 mm. Kata Kunci : Nasi Basi, Pupuk Organik, Tanaman, Bunga